PRIORITIZING CHILDREN’S BEST INTERESTS IN CANADIAN YOUTH JUSTICE: ARTICLE 3 OF THE UN CONVENTION ON THE RIGHTS OF THE CHILD AND CHILD-FRIENDLY ALTERNATIVES - Lacombe, Étienne F (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
The UN Convention on the Rights of the Child confers on children a number of rights, not the least of which is the guarantee that their best interests shall be a primary consideration in all actions that concern them. This article applies the Best Interests of the Child [BIC] principle—a widespread concept in family law—to the context of criminal policy. It calls for a rebalancing of Canadian youth justice so as to prioritize children’s best interests. As marginalized societal actors, children are at risk of seeing their interests increasingly overlooked if they are not brought to the fore. Once a defining feature of Canada’s response to juvenile delinquency, the BIC principle has waned in the face of sweeping penal populism. Examples from Scotland, Scandinavia and Washington reveal means by which child-friendly justice systems can withstand the influence of punitive public sentiment. Mirroring such approaches in Canada would require repurposing the deeply engrained concept of proportionality and viewing children’s interests as inherent to advancing public safety.